Strategy Implementation of Green Ethics Concept in Human Resource Management - Purnawati, Ni Luh Gede Putu Purnawati; Widnyani, Ni Made; Darmayanti, Ni Luh; Wahyuningsih, Luh Gde Nita Sri; Yudiastra, Putu Pande (Universitas Ibn Khladun Bogor, 2023)
The world is entering a transitional phase from the Industrial Revolution 4.0 to Society 5.0. One of the indicators of this transition is the emergence of various companies or organizations that make internal policies that are oriented towards increasing the value and welfare of their members. The strategy implemented is expected to stimulate the transition process to be faster and more measurable. Companies that want sustainability need to be consistent so that the policies implemented are in line with company goals. In this case, the policies designed are related to the development and management of human resources based on moral and ethical values (green ethics). This study aims to see what indicators are involved in implementing the policy and what steps should be taken by the Human Resource Development (HRD) team as the policy operator. The researcher uses a qualitative research method which is a description of the results of the literacy study to describe the research results more effectively. Based on the research results, green ethics policies have three key indicators as the main fundamentals, including green environment, green people, and green spirituality. The implementation of green ethics policies will be able to improve the quality of human resources which will indirectly help the company to remain sustainable.